Políticas públicas de financiamento da educação básica: uma análise da aplicação do Fundo de Manutenção e Desenvolvimento da Educação Básica e de Valorização dos Profissionais da Educação FUNDEB, no período 2007-2010, em Guajará-Mirim, RO - Gomes, Angela de Castro Correia (2011)
This study belongs to research line Public Politics and Education and Curricular Reforms. It aimed to elucidate how FUNDEB, a public policy focused on Basic Education, established in 2007/2009 was managed until 2010, in Guajará-Mirim, Rondônia state. The main goal was to identify possible interferences the Fund has caused in the education policy while under the referred municipal district responsibility, in the period from 2007 to 2010, such as: (a) analysis of incomes and expenses quantitative data; (b) attendance to school needs; (c) possible interferences in teaching value; and (d) understanding the resources administration regarding its technical aspects and of co-participative administration. The main goal was to make an evaluation of the technical administration as part of a public administration. It also focused on the importance of the democratic administration with co-participative bases in the education, particularly in the administration of public educational resources. It was also a discussion on public policy financing elementary education, mainly FUNDEB, regarding Brazilian public legislation and the financial competence of federal beings and on the process of substitution FUNDEB by FUNDEF, demonstrated by a comparison of a quantitative data of the municipal district, the State of Rondônia and entire country. It is a qualitative research, with a quantitative research support since it concerns an accounting Fund which includes, mainly number of registrations, analysis of tax incomes and expenses. The used methodology involved analysis of a number of Brazilian legislation documents concerning the elementary education and FUNDEB itself. We also searched about educational issues related to municipal area responsibility by (a) looking mainly at all the Municipal City hall accounting reports available, (b) by questionnaire application to schools and teachers and (c) interview with school principals', FUNDEB Council, Parents and Teachers Associations representatives and with municipal education managers. The results indicated that more than 90% of the expenses were payed with teaching effective personnel. It also indicated that the schools needs are not being fully assisted and that it lacks teaching materials/equipment, basic areas such as bathrooms, administration areas and cooking/dining hall; and that the students' low income lacks close monitorization. Most of the teachers are graduated and some have even masters degree but, not obtained with Fund resources. In 2010 it was implanted the Positions, Career and Wages Plan with wage adjustments based in the evolution of FUNDEB resources received by the municipal district. The democratic administration was considered important for the improvement of the municipal education, even if technical problems might interfere with its implantation. FUNDEB council members mentioned lack of technical capacity to interpret the incomes and expenses data accounting reports and to follow intern protocols focused on goods and services acquisition. Taken this, we might conclude that municipal district FUNDEB budget has been priority destinated to payment of teaching personnel